Building capacity in patient-oriented research: reflections on cultivating relationships within a high-secure forensic mental health hospital - Sevil Deljavan; Kayla Zimmermann; Amber Scott; Kristy Allen; Ryan Neil; Cara Evans; Elnaz Moghimi; Colleen Dell; Linzi Williamson; Christopher Canning (Research Involvement and Engagement)
Abstract Building trusting relationships is critical to the success of patient-oriented research. However, in high-secure forensic mental health settings, distrust, discrimination, and restrictive practices pose unique barriers to building relationships. This commentary explores the challenges, strategies, and lessons learned in fostering meaningful connections with forensic patients at a high-secure hospital. Initially focused on assessing readiness to conduct patient-oriented research, the team pivoted to relationship building, guided by the mentorship of peer researchers and patient advocates. Navigating institutional complexities, the team adopted a patient-centered approach informed by the principles of respect and human connection. Key strategies included shadowing experienced patient advocates embedded within the hospital, attending patient community meetings, and engaging in informal interactions with patients. These efforts enabled the team to move from observing interactions to engaging in patients’ daily lives through shared experiences. A major milestone was the successful planning and execution of a knowledge sharing event that brought together patients, staff, researchers, and external stakeholders to explore how to put patient-oriented research approaches into practice. Despite the progress, the team faced many challenges, including skepticism from staff and patients, and disruptions inherent to a high-secure environment. The commentary discusses critical lessons for overcoming these challenges, including the importance of patience, adaptability, and respecting boundaries. It emphasizes the intrinsic value of building relationships beyond research outcomes and advocates for incorporating diverse team expertise to foster trust and authentic connections. The commentary also highlights the perspectives of a current forensic patient and co-author, who shares how the team’s efforts made him feel valued as a person. His reflections add to the narrative by highlighting the impact of respectful interactions on relationships. By sharing these insights, this commentary aims to inspire other research teams to prioritize relationship building as a foundational step toward meaningful participatory research in forensic mental health care.